Pengaruh Perlakuan Jarak Tanam dan Pemberian Ekstrak Daun Mahkota Dewa Sebagai Penghambat Perkembangan Penyakit Antraknosa Pada Tanaman Cabai (Capsicum annum L) - Galvani Asep Santoni; Iin Arsensi; Mahdalena Mahdalena (Agrifarm : Jurnal Ilmu Pertanian, 2016)
Row spacing treatment had no significant effect on all parameters pengamatan.Pada age of 90 days after planting the average weight of the fresh fruit crop was obtained in treatment j2 highest ie 83.30 g, while the average weight of the fresh fruit crop obtained at the lowest possible j3 treatment of 75 , 49 g.Perlakuan extract of petals gods were not significantly affected all parameters pengamatan.Pada age of 90 days after planting the average weight of the fresh fruit crop was obtained in treatment d1 highest ie 83.98 g, while the average weight of the fresh fruit crop lowest was obtained in treatment that is 77.52 g.Interaksi d0 between the treatment plant spacing and crown god leaf extract had no significant effect on all parameters of observation. At the age of 90 days after planting the average percentage of disease were highest in j2d2 treatment combination that is 65.64% while the average percentage of the lowest in disease treatment combination j2d0 yaitu 51.72%. This research was conducted by randomized block design factorial 4 x 3 with three replications. The first factor is a spacing (A) which consists of three levels ie; j1 (60 x 60 cm), j2 (60 x 70 cm) and j3 (60 x 80 cm). The second factor is the extract of leaves of the gods crown (D), which consists of four levels ie; d0 (control), d1 (2 ml / liter of water), d2 (4 ml / liter of water) and d3 (6 ml / liter of water).